2009
DOI: 10.1093/europace/eup331
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results and the predictors of outcome of catheter ablation of atrial fibrillation using steerable sheath catheter navigation after single procedure in 674 patients

Abstract: In our patients' cohort, a single catheter ablation procedure based on CPVA using steerable sheath for catheter navigation resulted in a 1 year success rate of 75.7% [without (91.0%) and with (58.6%) early recurrence, respectively, P = 0.0001]. Among those patients who are at high risk for recurrence after CPVA other ablation endpoints rather than completion of predefined lesions might be necessary to increase the success rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 29 publications
7
86
3
4
Order By: Relevance
“…268,328,329,330 Conversely, patients with pharmacologically controlled hypertension could have similar risk of AF recurrence postablation as those without hypertension. 279 Pooled analysis of two small studies demonstrated that renal artery denervation resulted in both sustained lowering of BP and reduction in AF recurrence postablation.…”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
See 2 more Smart Citations
“…268,328,329,330 Conversely, patients with pharmacologically controlled hypertension could have similar risk of AF recurrence postablation as those without hypertension. 279 Pooled analysis of two small studies demonstrated that renal artery denervation resulted in both sustained lowering of BP and reduction in AF recurrence postablation.…”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
“…253,329,436,684,932,935,970,971,972 Because these arrhythmias do not definitively indicate therapy failure over the long term (only half of these patients will manifest later recurrences), this period is also referred to as the blanking or therapy stabilization period. 935,973 It is also important to recognize that the later AF recurrences are observed during the blanking phase, the lower the chance of long-term success.…”
Section: Early Recurrence After Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several months later he was subjected to catheter ablation of AF, due to the clinical suspicion of tachyarrhythmia-related cardiomyopathy. obesity, biochemical markers of inflammation, atrial fibrosis on MRI and increased CHADS 2 and CHA 2 DS 2 -VAS C score [18,74,[80][81][82][83][84]. Therefore, among younger patients with lone AF and normal or minimally remodelled LA, not only higher efficiency but also more stable long term effects of catheter ablation can be expected.…”
Section: Figure 3 Catheter Ablation Of Persistent Af: Pv Isolation Amentioning
confidence: 99%
“…9,10 With discontinuous and nontransmural ablation lines being one of the reasons for recurrences of AF and atrial macroreentrant tachycardia (MRT), steerable sheaths were designed to improve access to and contact with ablation target sites. 11,12 To build up scientific evidence on the clinical use of that technology, we published data from a retrospectively matched case-control analysis indicating a significantly superior rhythm control compared with an ablation approach with a nonsteerable sheath access.…”
Section: Clinical Perspective On P 165mentioning
confidence: 99%